Correlation of Total Fruit Vegetable Consumption with WHR & WTHR of Indonesian Nutrition Science Female Students - Widyastuti, Andhika Nara Vista; 'Aziz, Fathimah Nurul; Mardiyati, Nur Lathifah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: This project is aimed to determine the relationship between total consumption of fruit vegetable with waist to hip ratio (WHR) and waist to height ratio (WTHR) on female students of Muhammadiyah University of Surakarta (UMS) majoring nutrition program. Methodology: The research was observational with a cross-sectional design. A total of 45 samples used in this study. Data collections were taken by using identity questionnaire, anthropometry measurements of WHR and WTHR and fruit vegetable consumption obtained using a semi-quantitative food frequency questionnaire (SQFFQ). Analysis of data applied Spearman Rank correlation test.Results: All respondents consume fruits vegetables less than recommendations (<400gr/day). This study found that 13.3% and 28.9% respondents had abdominal obesity of WHR and WTHR, respectively. Respondent with WHR normal status were 86.7% and 71.1% of WTHR. Data analysis found that p-value = 0.825 for the relationship between the total of fruit vegetable consumption with WHR and p-value= 0.809 for the relationship between the total of fruit vegetable consumption with WTHR. There was no relationship between the total of fruit vegetable consumption with WHR and WTHR. Applications/Originality/Value: Basic data on the WHR and WTHR which can indicate the risk of abdominal obesity, especially in women and vegetable fruit processing methods must be considered as one of the factors that can affect the nutritional status.